Compact corrugatеd horn antenna initial design for microwave diagnostics in Uragan-2M stellarator - Pavlichenko, R.O.; Pavlichenko, N.I. (Problems of Atomic Science and Technology, 2023)
In this paper, a well-known design procedure is proposed for the design of wideband constant-beam width conical corrugated horn antennas, with minimum design and construction complexity. The inputs to the procedure are the operating frequency band, the required minimum beam width in the entire frequency band, and the frequency in which the maximum gain is desired to occur. Based on these values, the procedure gives a relatively good design with a relative bandwidth of up to 2.1:1 Based on the proposed procedure, a corrugated horn antenna with a constant beam width over the frequencies of 10 to 14 GHz was designed and simulated using commercial software. This paper presents initial design for the development of quasi-optical corrugated conical horn for reflectometry diagnostics for the Uragan-2M stellarator plasma experiments.